Clinical profile and treatment outcomes of acute lymphoblastic leukemia among children attending at the University of Gondar comprehensive specialized hospital and Tikur Anbessa Specialized Hospital in Ethiopia - Eyuel Kassa; Mulugeta Ayalew; Mastewal Birhan; Aschalew Gelaw; Abdulkader Mohammedsaid Gidey; Tadele Amare Zeleke; Degalem Tilahun Worku; Awol Mekonnen; Amare Kiflie; Ermias Teklehaimanot Yifter; Nega Berhane (PLoS ONE, 2025)
Background Acute lymphoblastic leukemia (ALL) is a common childhood cancer characterized by the uncontrolled proliferation of immature white blood cells. While advancements in treatment have significantly improved outcomes in developed countries, significant challenges remain in resource-limited settings, such as Ethiopia. This study aimed to assess the clinical profiles and treatment outcomes of ALL patients at the University of Gondar Comprehensive Specialized Hospital (UoGCSH) and Tikur Anbessa Specialized Hospital (TASH) in Ethiopia. A prospective longitudinal study was conducted among 179 ALL patients receiving treatment at the outpatient department and pediatric oncology centers of the UoGCSH and TASH between December 25, 2022, and August 30, 2024. Sociodemographic and clinical data were collected using a structured questionnaire. The data were entered and analyzed using SPSS version 25. Descriptive statistics were employed to summarize patient characteristics, while overall survival was evaluated using Kaplan-Meier analysis. Additionally, both univariate and multivariate Cox proportional hazards regression analyses were performed, with statistical significance set at a P-value of < 0.05. Results Among the 179 patients, 81 (45.3%) died during the course of treatment. Of these, 33 (18%) died before initiating induction therapy, while 48 (27.4%) died primarily due to treatment abandonment during various phases of therapy. The event-free survival rate was 75 (41.9%). Mortality rates were significantly higher in patients with certain variables identified through Cox regression analysis, including age, sepsis, and relapse, which nearly doubled the risk of death. Elevated LDH levels, malaria infection, and T-cell ALL were associated with approximately six-fold, three-fold, and seven-fold increases in the risk of death, respectively. Only 22 out of 179 patients (12.29%) achieved remission. Among these patients, hematotoxicities observed during the maintenance phase included anemia in 19/22 (86.4%), grade 3–4 neutropenia in 12/22 (52.2%), and thrombocytopenia in 17/22 (77.3%). Conclusion A high mortality rate was observed among children with ALL, with significant risk factors including relapse, age over 10 years, elevated LDH levels, sepsis, low platelet counts, T-cell ALL, malaria infection, and induction failure. To improve survival rates, it is essential to address these factors by optimizing treatment regimens and minimizing delays in diagnosis and care delivery.